Videoendoscopy evaluation of swallowing on oropharyngeal dysphagia approach - Freitas, Luís (2012)
Introduction: Oropharyngeal dysphagia can be interpreted as a disorder that difficult an efficient, comfortable and safe ingestion of any consistency of food or saliva. It is a symptom that may be related with an underlying congenital or acquired disease, permanent or temporary, or result from neurological, mechanical or psychogenic diseases, drug induced or due to age. It can compromise one or more phases. The knowledged of anatomy and physiology of swallowing is essential to an accurate diagnosis. In this paper we intend to demonstrate the usefulness of videoendoscopy of swallowing in the diagnosis and therapy in patients with oropharyngeal dysphagia.Methods: We present a serie of twenty patients who were referenced to our department with oropharyngeal dysphagia, between January and December 2011. Clinical evaluation was performed through clinically history and videoendoscopy evaluation of swallowing. In the classification of the severity an adaptation of Milton scale was used.Results: The patients had neurological and mechanical dysphagia and presbifagia; in relation to swallowing severety, 60% (12) had severe dysphagia, 25% (5) had moderate dysphagia and 15% (three) of the patients had mild dysphagia.Conclusion: Fiberotic endoscopy is a useful tool for examination, easily handled, with lower cost, that can be performed as the first method in the evaluation, diagnosis and therapeutic orientation in patients with this pathology. It is an important diagnostic approach for evaluation of dynamic and functional pharyngeal-laryngeal structures.